Children’s health perception through creative drawing language - Alves Rodrigues, Manuel Alves; Cruz Damas, Maria Dulce (Investigación y Educación en Enfermería, 2012)
Objective. Children’s health perception through creative drawing language the identification of external factors perceived as negative or positive to health by children. Methodology. A descriptive study that describes the analysis of the expressive language of drawings and written comments. The sample consisted of 130 children in 3rd and 4th classes from four randomly selected schools, in the region of Central Portugal Continental (Coimbra district). The study was conducted during the first semester of 2011. The data collection was performed by means of Rodrigues’ drawing/writing sheet. This sheet is divided in 4 areas (2 of them to draw what children consider good for health and the other 2 to write the content or message of the drawings). The themes expressed are classified based on the priority areas for the promotion of healthy lifestyles. Results. children value healthy food, physical activity, mental health, prevention of inappropriate substance consumption and health and environment. The drawings and comments show links between diet and physical exercise, and between mental health and interpersonal relationships. Conclusion. Drawings and comments facilitate health professionals understanding of children’s perception of health positive and negative factors. The results of the study allow planning intervention strategies in school health from infant perception.